1995
DOI: 10.1159/000288933
|View full text |Cite
|
Sign up to set email alerts
|

Visual Memory Impairment in Patients with Obsessive-Compulsive Disorder: A Controlled Study

Abstract: Memory processes were compared in 26 patients presenting DSM-III-R obsessive-compulsive disorder (OCD) with 20 sex-, age- and education-matched normal controls. A significant between-group difference was found: visual memory was significantly lower in OCD, whereas no significant between-group differences in verbal memory were observed. A subsample of 17 OCD were also compared with the 20 control subjects on an explicit-memory free-recall task and an implicit-memory completion task using neutral, obsessive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
2
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 13 publications
4
31
2
4
Order By: Relevance
“…[1][2][3] Other studies have reported nonverbal memory deficits. [4,5] Deficits in attention, visuospatial skills, and working memory have also been reported by several studies. [6][7][8] In contrast, one study found no evidence of neuropsychological abnormality in OCD.…”
Section: Introductionmentioning
confidence: 75%
“…[1][2][3] Other studies have reported nonverbal memory deficits. [4,5] Deficits in attention, visuospatial skills, and working memory have also been reported by several studies. [6][7][8] In contrast, one study found no evidence of neuropsychological abnormality in OCD.…”
Section: Introductionmentioning
confidence: 75%
“…This is consistent with previous research findings. Although verbal memory was initially assumed to be associated with compulsive checking [Sher et al, 1983], subsequent studies failed to corroborate this finding [Christensen et al, 1992;Dirson et al, 1995;Radomsky and Rachman, 1999;Sher et al, 1989]. However, several neuropsychological test results have consistently demonstrated impairments in nonverbal memory [Greisberg and McKay, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies failed to find evidence of memory deficits associated with OCD on measures of verbal memory [e.g., Abbruzzese et al, 1993;Dirson et al, 1995], word recognition [Foa et al, 1997], word recall [MacDonald et al, 1997;Zielinski et al, 1991], working memory , and recall of ''safe'' versus neutral objects [Tolin et al, 1999]. OCD washers and checkers have also shown some indication of having a positive memory bias toward remembering threat-relevant information [Radomsky et al, 2001;Radomsky and Rachman, 1999].…”
Section: Learning and Memory Deficits In Individuals With Ocdmentioning
confidence: 99%